2020
DOI: 10.1002/cplu.202000460
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Antiviral Material Development

Abstract: His current research interests include Environmental Impact Assessment, Toxicity, Waste Management, and Electrochemical applications. He has worked in various government-funded and consulting projects at NTU. He is trained in Life Cycle Assessment tools such as GaBi and SimaPro, Nanotools such as AFM, Ellipsometry, ATR-FTIR and QCMD, USEtox® 2.0-Characterization fact. Liya Ge obtained her B.Eng. in chemical engineering from Zhejiang University, China in 1999. From 1999-2002, she worked as an Engineer in State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 302 publications
(132 reference statements)
0
19
0
Order By: Relevance
“…AgNPs with and without polysaccharide coating (10–80 nm) blocked the penetration and binding of the virus-cell, indicating its potential use as antiviral therapy. Although antiviral materials' mechanisms are described with different terminologies in the literature, they boil down to competition or inhibition of the binding process between the virus and the host cell [ 16 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…AgNPs with and without polysaccharide coating (10–80 nm) blocked the penetration and binding of the virus-cell, indicating its potential use as antiviral therapy. Although antiviral materials' mechanisms are described with different terminologies in the literature, they boil down to competition or inhibition of the binding process between the virus and the host cell [ 16 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Peptides are compounds derived from natural sources such as bacteria, plants, and animals or synthesized rationally. They can interact with the virus, blocking the connection, and preventing viral fusion [ 16 ]. Besides, they may have biocidal activity, breaking the envelope of the virus.…”
Section: Materials With Antiviral Activitymentioning
confidence: 99%
“…The results shown that these polymers Additionally, one of the important applications of antiviral ability of PNC is to apply its layer in PPE, such as the mask fabrication to increase its ability to non-infectious and preventing viruses spreading. As an example, adding fourth layer to three layers mask structure that shown in Figure 18, to produce four layers mask structure that shown in Figure 19 [6,20]. An example of PNC that could use is based on nylon 6/poly acrylonitrile or polyethylene/polypropylene nanofibers layer that have been prepared by electrospinning-netting technique, as it were shown in Figure 20 [6].…”
Section: Pnc In Drug Systemmentioning
confidence: 99%
“…Depending on various antiviral mechanisms, numerous antiviral materials have been developed, such as metallic nanoparticles, carbon-based nanomaterials, organic nanomaterials, and antiviral biopolymers which were synthesized either artificially or extracted from natural resources [ 32 , 33 ]. Such functional nanomaterials are restricted always by high cost due to the complicated manufacturing process.…”
mentioning
confidence: 99%
“…Such functional nanomaterials are restricted always by high cost due to the complicated manufacturing process. In addition, though much attention has been paid to their unique physicochemical characteristics, nanomaterials are still questionable considering their potential toxicity toward humans and their environmental risk [ 33 , 34 ]. The large specific surface area of nanomaterials enables them to interact closely with intracellular substances, e.g.…”
mentioning
confidence: 99%